2017
DOI: 10.4103/ijem.ijem_476_16
|View full text |Cite
|
Sign up to set email alerts
|

Study of neutrophil-lymphocyte ratio as novel marker for diabetic nephropathy in type 2 diabetes

Abstract: Introduction:Diabetic nephropathy (DN) is a microvascular complication of diabetes. DN is clinically manifested as an increase in urine albumin excretion. Total white blood cell count is a crude but sensitive indicator of inflammation and studied in many cardiac and noncardiac diseases as an inflammatory marker such as acute myocardial infarction, stroke, and heart failure. In this study, the association of neutrophil-lymphocyte ratio (NLR) with DN is studied.Patients and Methods:It is an observational cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 44 publications
6
25
0
2
Order By: Relevance
“…NLR is a novel inflammatory marker known to be increased in patients with type 2 diabetes when compared with the healthy controls. NLR was also higher in patients with microalbuminuria group when compared with the normoalbuminuria group (Huang et al, 2015; Khandare et al, 2017). Our study found elevated levels of TNF-α, NLR, and IL-18 in patients with microalbuminuria and macroalbuminuria that were significantly higher than those detected in the healthy controls and type 2 diabetic patients with normoalbuminuria.…”
Section: Discussionmentioning
confidence: 85%
“…NLR is a novel inflammatory marker known to be increased in patients with type 2 diabetes when compared with the healthy controls. NLR was also higher in patients with microalbuminuria group when compared with the normoalbuminuria group (Huang et al, 2015; Khandare et al, 2017). Our study found elevated levels of TNF-α, NLR, and IL-18 in patients with microalbuminuria and macroalbuminuria that were significantly higher than those detected in the healthy controls and type 2 diabetic patients with normoalbuminuria.…”
Section: Discussionmentioning
confidence: 85%
“…The number of the included subjects in the case group and the control group ranged from 20 to 328 and 20 to 192, respectively. Of these 48 articles, 27 came from China [ 22 , 30 , 34 , 36 , 37 , 41 , 43–46 , 48 , 49 , 55–60 , 64 , 65 , 67 , 68 , 70–73 ], 16 from Turkey [ 21 , 23 , 29 , 31 , 35 , 38 , 40 , 42 , 47 , 50–54 , 61 , 69 ], 3 from India [ 32 , 63 , 39 ], 1 from Greece [ 62 ] and 1 from Kazakhstan [ 33 ]. Amongst these studies, 21 reported NLR (9 enrolled patients with DR, 12 enrolled patients with DN) [ 21 , 23 , 31 , 32 , 34 , 35 , 38 , 41–43 , 45 , 47 , 50–54 , 56–60 , 62 , 63 , 65 , 67–69 , 71–73 ], 33 reported the data of MPV (23 enrolled patients with DR, 10 enrolled patients with DN) [ 22 , 29 , 30 , 33 , 36–40 , 44 , 46 , 48–50 , 55 , 61 , 64 , 66 , 70 , 73 ], and 12 reported PDW (12 enrolled patients with DR, 3 enrolled patients with DN) […”
Section: Resultsmentioning
confidence: 99%
“…In T2DM, the increase in blood NLR and urinary IL-8 is of concern as high IL-8 can increase the progression of renal disease. 23,24 Renal damage and scarring are reported to be due to cytotoxic products of neutrophils. 25 A positive correlation between NLR and diabetic peripheral neuropathy has been recently suggested.…”
Section: Discussionmentioning
confidence: 99%